2017
DOI: 10.1016/j.bbi.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Salsalate treatment following traumatic brain injury reduces inflammation and promotes a neuroprotective and neurogenic transcriptional response with concomitant functional recovery

Abstract: Neuroinflammation plays a critical role in the pathogenesis of traumatic brain injury (TBI). TBI induces rapid activation of astrocytes and microglia, infiltration of peripheral leukocytes, and secretion of inflammatory cytokines. In the context of modest or severe TBI, such inflammation contributes to tissue destruction and permanent brain damage. However, it is clear that the inflammatory response is also necessary to promote post-injury healing. To date, anti-inflammatory therapies, including the broad clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…However, they most likely target the inflammatory phenotype of M1-like microglia and not neurons ( 4 ). Indeed, NF-κB inhibition in microglia and astrocytes has been shown to induce a beneficial outcome from CNS injuries ( 29 , 73 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, they most likely target the inflammatory phenotype of M1-like microglia and not neurons ( 4 ). Indeed, NF-κB inhibition in microglia and astrocytes has been shown to induce a beneficial outcome from CNS injuries ( 29 , 73 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies in oxytocin appear to be associated with psychiatric conditions involving deficits in social behavior including autism spectrum disorders and schizophrenia ( 84 86 ). Although findings in the literature lack consistency, recent research on both central and peripheral actions of oxytocin have identified potential relationships with mood and anxiety ( 87 ), learning and memory ( 88 ), improvement of wound healing ( 89 ), modulation of inflammatory responses ( 90 , 91 ), neuroprotection ( 89 , 91 , 92 ), regulation of food intake and body weight ( 93 ), and reduction of pain sensitivity ( 94 , 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in murine models have shown that salsalate, a non-steroidal anti-inflammatory drug (NSAID) reduces p-300 mediated acetylation of tau ( 30 ), resulting in improved cognition and reduced atrophy of brain regions such as the hippocampus. Lagraoui et al ( 86 ) reported similar findings in a murine model of traumatic brain injury (TBI) ( 86 ). Salsalate was shown to inhibit inflammatory pathways after TBI proximal to the injury site via reduction in microglia/macrophage activation.…”
Section: Future Directions In Potential Therapeuticsmentioning
confidence: 78%